If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3-2(x+8)=-15
We move all terms to the left:
3-2(x+8)-(-15)=0
We add all the numbers together, and all the variables
-2(x+8)+18=0
We multiply parentheses
-2x-16+18=0
We add all the numbers together, and all the variables
-2x+2=0
We move all terms containing x to the left, all other terms to the right
-2x=-2
x=-2/-2
x=1
| x*0.15=35 | | 3a+4=-2a+9 | | -4y+6=35y-3 | | 4x+1/2(8x+)=2(4x+3 | | 17-2p=2p-5-2p | | 2y+9=8y+29 | | 4g-2=2g+8 | | 3+4x=-2x-9 | | -7n+6n=-7-5 | | 4a+2a=180 | | -3k-2=2*k+2 | | -9=c+-8 | | 12u+2=7u+22 | | 6u-3u+5=20 | | -2z+3=7 | | -2=(1/x+3) | | 0.5h-1=0.4h+5 | | 6/4x+x=12 | | 16s+-4s+-19=5 | | F(x)=2x+x/3 | | 4(5-2x)=-4 | | 135-5x=90 | | 16x+4=2x-8 | | 9r-10r-11r+-20=-8 | | 3/4(9x+15)-7x=45 | | N—-4=16,n | | (x+1)+(5x+5)=7x-3 | | 16x-4=2x+8 | | 5x2+4x+-10=0 | | -2(8x-3)=10 | | -8y-16y-9y+14y-(-10y)=18 | | 5x+x-7=10+13 |